Miniaturized band‐pass filter based on composite right‐/left‐handed transmission‐line unit cell. Issue 7 (July 2015) - Pandey, Arvind Kumar; Gaurav, Yatindra; Chauhan, R. K.
ABSTRACT This article presents the design and implementation of a band‐pass filter using a novel composite right‐/left‐handed (CRLH) structure. To minimize the overall size of filter, the concept of CRLH metamaterial is used. Only one unit cell of CRLH is used in this filter to reduce size. The proposed CRLH structure for this filter shows smaller size than the filters designed using traditional methods. The designed filter is simulated and, thereafter, validated by physical realization and its testing. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1713–1717, 2015